Peculiarities of the volume magnetostriction in La₁₋xSrxMnO₃ in the Curie point region - Koroleva, L.I.; Abramovich, A.I.; Demin, R.V.; Michurin, A.V. (Физика низких температур, 2001)
The parallel λ∥ and perpendicular λ⊥ magnetostriction (with respect to the applied magnetic field) and the thermal expansion Δl/l are studied on La1−xSrxMnO₃ single crystals with x=0.1, 0.15, and 0.3. For the conducting sample with x=0.3 and the semiconducting sample with x=0.15 the volume magnetostriction (ω=λ∥+2λ⊥) is negative and the |ω|(T) curves go through a maximum at the Curie point TC. At T>TC its Δl/l temperature dependence is stronger than linear. For the semiconducting sample with x=0.1, ω is negative at T<TC and |ω|→0 at T∼TC. Its Δl/l is linear at T<=TC. The behavior of ω and Δl/l are explained by a magnetic two-phase state, due to strong s−d exchange.